Differential regulation of hepatic physiology and injury by the TAM receptors Axl and Mer - Zagórska, Anna (Life Sci Alliance, 2020)
Genome-wide association studies have implicated the TAM receptor tyrosine kinase (RTK) Mer in liver disease, yet our understanding of the role that Mer and its related RTKs Tyro3 and Axl play in liver homeostasis and the response to acute injury is limited. We find that Mer and Axl are most prominently expressed in hepatic Kupffer and endothelial cells and that as mice lacking these RTKs age, they develop profound liver disease characterized by apoptotic cell accumulation and immune activation. We further find that Mer is critical to the phagocytosis of apoptotic hepatocytes generated in settings of acute hepatic injury, and that Mer and Axl act in concert to inhibit cytokine production in these settings. In contrast, we find that Axl is uniquely important in mitigating liver damage during acetaminophen intoxication. Although Mer and Axl are protective in acute injury models, we find that Axl exacerbates fibrosis in a model of chronic injury. These divergent effects have important implications for the design and implementation of TAM-directed therapeutics that might target these RTKs in the liver.